Expanded Sampling Across Ontogeny in Deltasuchus motherali (Neosuchia, Crocodyliformes) Revealing Ecomorphological Niche Partitioning and Appalachian Endemism in Cenomanian Crocodyliforms - Drumheller, Stephanie K. (Physical Sciences, 2021)
A revised diagnosis of this species, describing the new material and discussing incidents of apparent ontogenetic variation across the sampled population. The results of the ensuing phylogenetic analyses both situate Deltasuchus within an endemic clade of Appalachian crocodyliforms, separate and diagnosable from goniopholidids and pholidosaurs. This title is also available as Open Access on Cambridge Core.